2021
DOI: 10.1155/2021/8905578
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] MKP‐1 Overexpression Reduces Postischemic Myocardial Damage through Attenuation of ER Stress and Mitochondrial Damage

Abstract: Mitochondrial dysfunction and endoplasmic reticulum (ER) stress contribute to postischemic myocardial damage, but the upstream regulatory mechanisms have not been identified. In this study, we analyzed the role of mitogen-activated protein kinase (MAPK) phosphatase 1 (MKP-1) in the regulation of mitochondrial function and ER stress in hypoxic cardiomyocytes. Our results show that MKP-1 overexpression sustains viability and reduces hypoxia-induced apoptosis among H9C2 cardiomyocytes. MKP-1 overexpression attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Dual-specificity protein phosphatase 1 (DUSP1), also termed mitogen-activated protein kinase phosphatase 1 ( 17 , 18 ), is involved in numerous physiological and pathological processes, including endoplasmic reticulum stress ( 19 ), microglial polarization ( 20 ), homeostasis and inflammation ( 21 ). Dysfunction of DUSP1 may induce several diseases, including neuro-inflammation ( 22 ), renal fibrosis ( 23 ) and rheumatoid arthritis ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dual-specificity protein phosphatase 1 (DUSP1), also termed mitogen-activated protein kinase phosphatase 1 ( 17 , 18 ), is involved in numerous physiological and pathological processes, including endoplasmic reticulum stress ( 19 ), microglial polarization ( 20 ), homeostasis and inflammation ( 21 ). Dysfunction of DUSP1 may induce several diseases, including neuro-inflammation ( 22 ), renal fibrosis ( 23 ) and rheumatoid arthritis ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%